The Cobalt Enrichment Zone of Gag Island, West Papua, As A Valuable Mineral Resource (Science and Technology (SciTech), 2023)
Abundant cobalt reserves, especially those associated with nickel laterite, have significant potential in the cobalt industry. The demand for cobalt is expected to increase in the world market along with the increasing use of electric cars. This research was conducted using primary data collection methods in the field as well as descriptive quantitative methods with a literature study approach and are descriptive in nature by conducting in-depth studies and studies of the potential for cobalt on Gag Island. Laterite deposits contain garnierite minerals which are rich in nickel such as on Gag Island where the concentration of cobalt is relatively high. Cobalt is anticipated to dissolve and migrate more significantly in hot and humid environments which could lead to increased concentrations of cobalt in laterite deposits such as those in the Gag Islands. For example, the solubility and precipitation of cobalt can be affected by the pH (acidity) of the solution and the amount of oxygen present in the environment. Geochemical analysis of laterite nickel drill with cobalt (Co) elements in the study area. Nickel-containing rocks weathered in hot and humid environments, a layered structure known as a nickel laterite profile is created from top to bottom. Solutions containing cobalt can pass through laterite layers, especially through pores and cracks in the rock.